The Effects of a Training Levy on Training Characteristics and Outcomes: The Case of Quebec - Gagnon, Marie-Eve; Smith, Michael (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2013)
SummaryIn this article, we compare the characteristics of workplace-provided training and its effects on wages in Quebec with other Canadian provinces. It is widely argued that training tends to be under-provided by employers. The institutions of training provision vary across Canada. Quebec is most distinct. With Law 90, it attempted to address what was seen as a distinctly severe problem of under-supply; it required that firms invest a specified proportion of their sales in training or turn over the difference between what they spent and the specified proportion to the government. We use data from the Workplace and Employee Survey to explore the possible effects of this measure. There are differences between Quebec and the other provinces in the incidence of on-the-job and formal training, and in the relations between training and the wage rate. In Quebec, the incidence of on-the-job training is distinctly low and the use of external training providers distinctly high. We suggest that these outcomes are encouraged by Law 90, which encourages employers to use readily documentable forms of training. We also find that the association between on-the-job training and the wage rate is much stronger in Quebec than in the comparator provinces. We argue that this is probably because, being less abundantly provided, on-the-job training is likely to be provided to employees who, on average, are more talented than their counterparts in the rest of Canada. We set our discussion of the possible effects of Law 90 in the context of a broader consideration of the relation between institutions and training choices and outcomes, including international comparison.